Comparison of the efficacy and safety of 10 glucagon-like peptide-1 receptor agonists as add-on to metformin in patients with type 2 diabetes: a systematic review - Xie, Zeyu; Hu, Jia; Gu, Hangye; Li, Mengting; Chen, Jisheng (Frontiers in Endocrinology, 2023)
Purpose: This study aimed to perform a network meta-analysis to objectively evaluate the efficacy and safety of 10 Glucagon-like peptide-1 receptor agonists (GLP-1RAs) in combination with metformin that is approved for use worldwide in patients with type 2 diabetes and to provide evidence-based support and reference for the selection of clinical treatment.Methods: Three databases (PubMed, Embase, and Cochrane Library) were searched from their respective inception until September 30, 2022. Only randomized controlled trials comparing the efficacy and safety of GLP-1RAs for treating type 2 diabetes (T2D) were included. The 10 GLP-1RAs are exenatide (including exenatide twice daily and once weekly), liraglutide, lixisenatide, dulaglutide, PEX168, semaglutide (subcutaneous and oral semaglutide), tirzepatide and albiglutide.Results: 34 RCTs with 10 GLP-1RAs and 12993 patients were included in the Network Meta-Analysis (NMA). According to the NMA, tirzepatide 15 mg, semaglutide 1.0 mg, PEX168-200μg, oral semaglutide 14 and dulaglutide 1.5 mg reduced HbA1c by -2.23%, -1.57%, -1.12%, -1.10%, -1.09% and body weight by -11.33 kg, -5.99 kg, +0.40 kg, -3.95 kg, -1.87 kg, respectively. There was no significant difference in the rate of adverse events for tirzepatide 15 mg, oral-semaglutide 14 mg, and semaglutide 1.0 mg. PEX168-200μg, tirzepatide 15mg, and oral semaglutide 14mg had Surface Under the Cumulative Ranking (SUCRA) values greater than placebo, and only tirzepatide 15mg and oral semaglutide 14mg were significantly different from placebo in the rate of serious adverse events. All GLP-1RA did not lead to increased incidence of hypoglycemia. Albiglutide 30mg and semaglutide 1.0mg significantly differed from placebo in Adverse Event (AE) withdrawal. Finally, the sensitivity analysis and publication bias analysis results indicate that the study results are reliable.This study's results showed that GLP-1RAs were effective in lowering HbA1c and reducing body weight without increased incidence of hypoglycemic reactions. In addition, this study may provide reference and evidence-based medical evidence for clinicians to select GLP-1RAs in patients with T2D and high body mass index (BMI). Based on the NMA results, tirzepatide 15mg and semaglutide 1.0mg may be preferred.